PROFIL DAERAH DAN RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS DI PEMERINTAH PROVINSI DI INDONESIA - Sari, Diah Novita; Murtanto (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2024)
Based on the regional fiscal capacity map from 2016 to 2022, the provinces in Indonesia that classified as high and very high fiscal capacity categories no more than 11 or 32% of the total number of provinces in Indonesia. Low fiscal capacity limits the government's ability to provide public services, hampers long-term growth, and reduces the ability to manage economic fluctuations effectively. Those conditions can lead to financial distress. This study intends to analyse financial ratios and regional profiles, specifically the effects of the government age, area size, population, current ratio, operating revenue ratio to total revenue, revenue growth, efficiency ratio, financial independence, and degree of decentralization on financial distress. SPSS 25 is utilized for conducting hypothesis testing through binary logistic regression analysis. This study finds that area size, population, revenue growth, financial independence, and degree of decentralization, have negative impact on financial distress. Conversely, the efficiency ratio shows positive impact on financial distress. The current ratio and operating revenue ratio to total revenue does not have impact on financial distress. These findings imply the need to improve the revenue, efficiency, and financial independence of local governments and to implement fiscal policies that support decentralization to reduce the risk of financial distress. Future researchers are advised to expand the research and to explore other variabels such as unemployment rate, poverty rate, and Gini ratio.